Comparative macromolecular composition of filaments and rods of a Bacillus megaterium thermoconditional morphological mutant. - Yan, L P (1980)
Filaments of a thermosensitive Bacillus megaterium mutant showed an altered macromolecular composition compared with salt-cured mutant cells and parental cells. Filaments contained more peptidoglycan, polyglucose, poly-beta-hydroxy-butyrate, and deoxyribonucleic acid per unit of protein. The ribonucleic acid-to-protein ratio of filaments was similar to that of rods or salt-cured cells. Filament formation seemed to be due to defective protein or ribonucleic acid metabolism.